Cryopreservation of Potato Shoot Tips for Long-Term Storage - Vollmer, R.; Espirilla, J.; Villagaray, R.; Cárdenas, J.C.; Castro, M.; Sánchez, J.C.; Manrique, N.; Ellis, David (Springer, 2021)
Cryopreservation is currently the only method which allows long-term conservation of living clonal plant material in the vapor or liquid phase of nitrogen (at −140 to −196 °C) allowing tissue to be viable for decades or perhaps centuries. Specifically, for species with recalcitrant seeds or requiring constant vegetative propagation, it is the method of choice for the long-term conservation of its genetic resources. The protocol described here is a modification of a previously developed plant vitrification solution 2 (PVS2)—droplet vitrification method of potato shoot tips, adapted from Musa species. Utilizing this protocol, the International Potato Center (CIP) has successfully stored in the cryobank more than 3000 cultivated potato accessions, belonging to seven species and nine different taxa [16], originating principally from ten countries in South and Central America. As part of CIP’s quality management system, all vegetative material placed in cryo is routinely subsampled, thawed, and assessed to confirm that whole plantlets can be produced after storage in liquid nitrogen. Complete plant recovery rates of thawed shoot tips range from 20% to 100% (average rate: 60%). This chapter describes the complete set of steps from the routine procedure of cryopreserving potato shoot tips for long-term conservation.